2022
DOI: 10.3390/nano12071142
|View full text |Cite
|
Sign up to set email alerts
|

Metal-organic Framework ZIF-67 Functionalized MXene for Enhancing the Fire Safety of Thermoplastic Polyurethanes

Abstract: In this work, a novel functionalization strategy for ZIF-67-modified layered MXene was proposed, aiming at improving the fire safety of thermoplastic polyurethanes (TPU). The ZIF-67@MXene was verified by microscopic morphology, elemental composition, functional group species and crystal structure, and then the successfully prepared ZIF-67@MXene was introduced into the TPU material. When ZIF-67@MXene content was only 0.5 wt%, the peak heat release rate, total heat release rate, peak smoke release rate, total sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…4e and Fig. S2a, ESI †), four main peaks were observed located at 455.18, 458.13, 460.85, and 463.64 eV, corresponding to Ti-C, Ti-O/F, Ti-C, and Ti-O bonds, 55 respectively. Compared to pure MXene, the increase in Ti-O bonds may be caused by the following two factors: 56 (1) MXene was significantly oxidized; (2) the terminal block was replaced by Ti-O.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4e and Fig. S2a, ESI †), four main peaks were observed located at 455.18, 458.13, 460.85, and 463.64 eV, corresponding to Ti-C, Ti-O/F, Ti-C, and Ti-O bonds, 55 respectively. Compared to pure MXene, the increase in Ti-O bonds may be caused by the following two factors: 56 (1) MXene was significantly oxidized; (2) the terminal block was replaced by Ti-O.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the interaction between electric dipoles and electromagnetic wave electric fields, or the interaction between magnetic dipoles and electromagnetic wave magnetic fields, the absorption of electromagnetic waves will be increased, which can help achieve the purpose of electromagnetic shielding. [36][37][38][39] For example, Song et al 40 prepared a Fe 3 O 4 @Ti 3 C 2 T x /rubber composite with a three-dimensional (3D) isolated interconnect structure. Due to the doping of magnetic nano Fe 3 O 4 , its EMI SE in the X-band was up to 58 dB.…”
Section: Introductionmentioning
confidence: 99%
“…The I D /I G ratio reects the graphitization degree of the char residue, where lower I D /I G ratios correspond to a higher graphitization degrees. 47,48 According to Fig. 6(a)-(c), the ID/IG values for pure EP, EP/ APHZ-1, and EP/APHZ-3 were 2.9, 2.6, and 2.5, respectively.…”
Section: Flame Retardancy Mechanismmentioning
confidence: 97%
“…These findings indicate the intricate coexistence of various phosphorus derivatives inside of the residual char. In Figure 6g, it is observed that N elements are predominantly present in the form of pyrrolic N and pyridinic N, 43 implying that Ti 3 C 2 T x promotes the formation of heterocyclic structures within the solid phase to protect the char layer during combustion. Furthermore, the N−B signal is detected at 399.0 eV, 44 suggesting that an organic boron structure might form a boron nitride derivative in a ceramic form at high temperatures.…”
Section: Flame Retardant Mechanismmentioning
confidence: 99%